The Russian Province After Communism - Edwards, Vincent. author. aut Link
X, 203 p.
Keywords: This book investigates the responses of companies in Russia's Volgograd (formerly Stalingrad) province to the fundamental changes in the economic system and is based primarily on interviews with local managers and decision-makers. Company case studies explore the impact of change on the conduct of business and are related to general developments in the economy. The book also questions the future development of Russian companies in a situation of tension between the resilience of the past and enormous pressures for change.